Functional characterization of SMARCA4 variants identified by targeted exome-sequencing of 131,668 cancer patients - Tharu M. Fernando (Nature Portfolio, 2020)
SMARCA4 is the core catalytic subunit of the mammalian SWI/SNF complex and is known to be mutated in many cancers. Here, the authors detect more than 10,000 SMARCA4 variants across different cancer subtypes and find hotspot mutations throughout the helicase domain, which reduce remodeling activity.